Gestão da informação e inteligência competitiva em empresas de biotecnologia do Brasil - Oliveira, Maria Fernanda de (Universidade Federal de São Carlos, 2012)
Through the perception of the value and potential of Biotechnology for Brazil and the lack of studies concerning politics, economy and social affairs in this area, this research has the intention of studying the Biotechnology companies from the point of view of their information management and relationship with Financiadora de Estudos e Projetos (FINEP), major sponsor, based in the hypothesis that there might be some difference between companies that receive and companies that do not receive financial resources from FINEP regarding information and market position. The methodology applied can be defined as descriptive and exploratory, with quality and quantity analysis. The data was collected through the organization of secondary information and research in specific literature and official web sites, content analysis form and a questionnaire applied via websurvey to 52 biotechnology companies set as statistic sample. The analysis was based in simple statistic, reflected average and official announcements and free answers checking. The results obtained from the Brazilian biotechnology companies were in general geographic location and legal nature. Regarding the companies taken as sample, the results were: the companies managers graduation; geographic market comprehended by these companies; business size; their relationship with FINEP; identified obstacles to their development and information management uses and competitive intelligence executed. Besides these results, there is a resumed analysis over the FINEP official announcements with the identification of their main characteristics. The main conclusions shows that the FINEP official announcements have clear structure about the necessary items and means of evaluations applied, as well as a schedule for all the process. The FINEP and Non-FINEP companies have similar practices when dealing with information, including informal and non-coordinated actions. This reality can be one of the reasons that colaborate to a difficulty in elaborating proposals to FINEP for there is lack of good and appropriate information to develop adequate proposals. However, it could be noticed that the competition among the biotechnology companies is high, what tends to be linked to a market highly focused in innovation. Thus, theoretical constructions were integrated with the information obtained with the research, generating a simplified model of information management with recommendations looking forward to structuring the actions involving the informational practice in companies. It is expected that the results presented can strenghten the data collection of the companies as well as the use of information, promoting better decisions about FINEP and some perceptions to contribute the elaboration of official announcements to this area.
Keywords: Gestão da informação; Biotecnologia - empresas; Inteligência competitiva; FINEP; Inteligência Competitiva; Competitividade empresarial; Competitive intelligence; Information management; Biotechnology companies Brazil; FINEP; Business competitivity; CIENCIAS SOCIAIS APLICADAS::CIENCIA DA INFORMACAO